A modified tarsal sinus approach for intra-articular calcaneal fractures - Junfeng Zhan; Chuanzhen Hu; Nan Zhu; Wang Fang; Juehua Jing; Gang Wang (Journal of Orthopaedic Surgery, 2019)
Background: Plate fixation using traditional lateral L-shape approach for intra-articular calcaneal fractures is complicated by 30% of wound complications, and the lateral small incision techniques with a tarsal sinus approach cannot sufficiently address all the fragments. A modified tarsal sinus approach with combined advantages of traditional lateral L-shape and tarsal sinus approaches for the treatment of intra-articular calcaneal fractures was developed. Method: This prospective study included 29 patients (13 Sanders type II and 16 type III) with calcaneal fractures were managed with this technique. Calcaneal height, width, length, Bohler’s angle, and Gissane angle were measured preoperatively, postoperatively, and at 1-year follow-up. Functional outcomes were assessed based on American Orthopedic Foot and Ankle Society (AOFAS) ankle/hindfoot score. Results: Twenty-nine patients with average follow-up time of 18 (range 13–29) months were included. The radiographs demonstrated significant corrections of the Bohler’s angle and Gissane angle, calcaneal width, length, and height from preoperation to postoperation and 1-year follow-up. Among all follow-up patients, one case had skin necrosis but healed after dressing. Another case had symptoms of numbness in the sural innervation area, which disappeared after 5 months of physical therapy and drug therapy. One case showed degenerative changes of subtalar joint at 1-year follow-up. No other wound complications like incision infection (superficial or deep) and wound dehiscence occurred. At 1-year follow-up, the mean AOFAS score was 90.2 ± 17.7 (range 70–98) and the good and excellent rate was 89.7%. Conclusion: The modified tarsal sinus approach in the treatment of Sander’s type II and III calcaneal fractures allowed adequate reduction and rigid fixation with low incidence of wound complications. Compared to sinus tarsi approach, this technique required shorter learning curve and was more easily mastered by young orthopedic surgeons. Thus, it was worthy of application clinically.